Аналіз способів подачі субстрату в метантенк біогазової установки - Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Skliar, Radmila (ТДАТУ, 2020)
UK: В статті проаналізовані основні способи подачі субстрату в метантенк біогазової установки з метою виявлення переваг та недоліків кожного з них. Отримано, що спосіб подачі субстрату за допомогою резервуару для зберігання має наступні особливості: непроникний для гною, працює з рідким гноєм або кількість доданого твердого субстрату невелика; чим вище відсоток вмісту сухої речовини в косубстраті, тим більше робочого часу необхідно буде витратити на його переробку. При аналізі способу непрямої подачі розглянуті варіанти з замивною шахтою, установками для замивання закритого типу та подачею твердих субстратів по трубопроводу під тиском. Особливостями останнього є: можливість одночасного подрібнення, перемішування і змішування з рідиною; подача субстратів може реалізовуватися довільно. Також проаналізовано пряму подачу за допомогою шнекових транспортерів з накопичувальним бункером, реконструйованих мішалок для корму, дозувальних станцій та гідравлічних систем. Особливості такого способу подачі: повинна бути непроникною для рідини (або газу), місце розташування поруч з реактором, можливо вагове дозування. RU: В статье проанализированы основные способы подачи субстрата в метантенк биогазовой установки с целью выявления преимуществ и недостатков каждого из них. Получено, что способ подачи субстрата с помощью резервуара для хранения имеет следующие особенности: непроницаемый для навоза, работает с жидким навозом или количество добавленного твердого субстрата небольшое; чем выше процент содержания сухого вещества в косубстрате, тем больше рабочего времени необходимо будет потратить на его переработку. При анализе способа непрямой подачи рассмотрены варианты с замывной шахтой, установками для замывания закрытого типа и подачей твердых субстратов по трубопроводу под давлением. Особенностями последнего являются: возможность одновременного измельчения, перемешивания и смешивания с жидкостью; подача субстратов может реализовываться произвольно. Также проанализирована прямая подача с помощью шнековых транспортеров с накопительным бункером, реконструированных мешалок для корма, дозирующих станций и гидравлических систем. Особенности такого способа подачи: должна быть непроницаемой для жидкости (или газа), местоположение рядом с реактором, возможно весовое дозирование. EN: The article analyzes the main ways of feeding substrate into the digester of a biogas plant with the aim of identifying advantages and disadvantages of each. Justified the choice of the optimum technique for submission will depend not only on the substrate and its quantity, cost, location and the like, but also on the intentions and the working time of the enterprise Manager. Analyzed the method of delivery of substrate via the storage tank and identified the following features of the implementation: impervious to manure, the gas impermeability is not needed, working with liquid manure or the amount of solid substrate added is small, the cylindrical shape facilitates the mixing processes; the higher the percentage of the dry substance in cosubstrate, the more time must be spent on recycling in the pre-tank storage. If there is kofermenta large quantities of solid substrate in the tank pre-storage you need to add additional (increased) number of liquid substances, with the aim of obtaining suitable for mass flow. In the analysis of the indirect way of submission to the digester variants are considered slivnoy mine, facilities for sumivka closed and the flow of solid substrates through the pipeline under pressure. Problematic for samineh mines is the portion of the flow without the possibility for accumulation with resultant emission of odors during zalivanii. The main disadvantage of the supply of solid substrates through the pipeline under pressure is the sensitivity of foreign objects (stones, materials with long fiber, metal parts). Latest features are: simultaneous grinding, mixing and mixing with liquid; the flow of solid substrates can be realized arbitrarily; flow liquid fraction separate pump. Also analyzed the direct supply by means of a screw conveyor with storage hopper, rebuilt mixers for feed, metering stations and hydraulic systems. Features of this method of submission: must be impervious to liquid (or gas), location near the reactor, possibly weighted metering and the like.
Анализ способов подачи субстрата в метантенк биогазовой установки
Analysis of methods for submitting substrate into the methane of the biogas installation
Keywords: біогаз; установка; метантенк; твердий субстрат; резервуар; подача; транспортування; рідина; биогаз; твердый субстрат; транспортировка; жидкость; biogas; installation; digester; solid substrate; reservoir; feed; transportation; liquid